Global Forum for Physical Education Pedagogy 2010 - Chen Chee, Keong (Pusat Pengajian Sains Perubatan, 2010)
Qualified and Dedicated Teaching Staff- Selection of health and physical education (HPE) teachers and the training program for this discipline should be given due consideration. This will ensure that the HPE teachers are well-trained with the right attitude so that the students will derive maximum benefit from the HPE lessons.